Implementation of Markerless Augmented Reality For Human Anatomy Education - Almesta, Adhika Yameraja; Bachri, Otong Saeful; Ramdhan, Nur Ariesanto (CV. Publikasi Indonesia, 2025)
This research aims to develop and implement Augmented Reality (AR) technology as an interactive learning medium for introducing human body anatomy using a markerless method. The background of this research is the lack of interest and understanding among students regarding biology, particularly anatomy, which has been delivered through conventional methods such as textbooks or two-dimensional images. AR technology allows students to visualize three-dimensional models of human body parts directly in the real world, without the need for physical markers, thereby creating a more engaging, flexible, and accessible learning experience. The methods used in this research include planning stages, needs analysis, data collection through interviews and observations, application development using Unity and Vuforia SDK, and finally implementation and evaluation. The application developed was tested at SMAN 1 Bulakamba and resulted in an increase in students' understanding and interest in learning anatomy. The evaluation results show that the majority of students stated they understood the material very well after using this AR application, with high average scores on each questionnaire indicator. Thus, the application of markerless AR technology has proven effective as an interactive visual education tool and holds great potential for implementation in biology education as well as other subjects that require complex visualizations